Comparison of blood and lymph node cells after intramuscular injection with HIV envelope immunogens - Day, Suzanne; Kaur, Charandeep; Cheeseman, Hannah M.; de Groot, Emily; McFarlane, Leon R.; Tanaka, Maniola; Coelho, Sofia; Cole, Tom; Lemm, Nana-Marie; Lim, Adrian; Sanders, Rogier W.; Asquith, Becca; et al. (Frontiers in Immunology, 2022)
Background Harnessing CD4+ T cell help in the lymph nodes through rational antigen design could enhance formation of broadly neutralising antibodies (bNAbs) during experimental HIV immunisation. This process has remained hidden due to difficulty with direct study, with clinical studies instead focusing on responses in the blood as a proxy for the secondary lymphoid tissue. Methods To address this, lymph node cells (LNC) were collected using ultrasound guided fine needle aspiration of axillary lymph nodes from 11 HIV negative participants in an experimental HIV immunogen study (European AIDS Vaccine Initiative EAVI2020_01 study, NCT04046978). Cells from lymph node and blood (PBMC), were collected after intramuscular injection with HIV Env Mosaic immunogens based on HIV Envelope glycoprotein and combined with a liposomal toll-like receptor-4 adjuvant; monophosphoryl lipid A. Simultaneously sampled cells from both blood and lymph node in the same donors were compared for phenotype, function, and antigen-specificity. Results Unsupervised cluster analysis revealed tissue-specific differences in abundance, distribution, and functional response of LNC compared with PBMC. Monocytes were virtually absent from LNC, which were significantly enriched for CD4+ T cells compared with CD8+ T cells. Germinal centre T follicular helper cells were enriched in LNC, which contained specific CD4+ and CD8+ T cell subsets including CD4+ T cells that responded after a single injection with HIV Env Mosaic immunogens combined with adjuvant. Tissue-specific differences in response to an MHC-II dependent superantigen, staphylococcal enterotoxin B, indicated divergence in antigen presentation function between blood and lymph node. Conclusions LNC are phenotypically and functionally distinct from PBMC, suggesting that whole blood is only a limited proxy of the T cell lymphatic response to immunisation. HIV-specific CD4+ T cells in the lymph node are rapidly inducible upon experimental injection with HIV immunogens. Monitoring evolution of CD4+ T cell memory in LNC with repeated experimental HIV immunisation could indicate the strategies most likely to be successful in inducing HIV-specific bNAbs.